Heritage-making 'from below': the politics of exhibiting architectural heritage on the Internet – a case study. Issue 3 (15th March 2016) - Aigner, Anita
Abstract: The 'digital revolution' created new opportunities for private persons to participate in the public discourse on architecture and architectural heritage. But has this new 'participatory culture' also triggered democratic polyphony and a questioning of dominant (expert) values and knowledge? And when considering official Internet representations – is there a proactive policy involving citizens? Taking the 'virtual life' of the Vienna Werkbund estate (1932), a modernist icon listed as a national monument in 1978, as a case study, the present examination tempers exaggerated hopes. The analysis of private and official websites shows that new information and communication technologies foster the expression of different viewpoints only to a limited extent. Although residents use the Internet to voice criticism, actors situated outside expert culture primarily reaffirm the estate's cultural value and act as co-producers of the dominant discourse. Focusing on official heritage, this paper not only provides evidence for the perpetuating function of new digital tools but also reveals the power relations that underpin paternalistic cultural mediation. Given the technological possibilities of involvement, it criticises official web representations for the exclusion of 'the public' and raises the fundamental question of what the digital mediation of cultural heritage in democratic societies should look like.